Analysis of Organizational Culture and Work Environment on Employee Performance : Case study at Duren Sawit District Office, East Jakarta - Armaniah, Henny; Melyani, Melyani; Yulianto, Andri Rizko; Nikmah, Wasilatun; Subariyanti, Herudini; Yulianto, Yulianto (University of Science and Computer Technology, 2025)
This study investigates the influence of organizational culture and work environment on employee performance at the Duren Sawit District Office. Anchored in Social Cognitive Theory, this quantitative research employed a census method, surveying all 85 employees. Data were analyzed using multiple linear regression. The results revealed that both organizational culture and work environment have a significant and positive partial and simultaneous effect on employee performance. The model explained 52.4% of the variance in performance, confirming that a conducive workplace context significantly predicts employee behavior.